Developing a sustainable model of Waqf-based Takaful for flood victims in Malaysia - Che Mohd Salleh, Marhanum; Razali, Siti Salwani; Megat Laksana, Nan Noorhidayu; Che Embi, Nor Azizan; Abdullah, Nurdianawati Irwani (Emerald Group Publishing Ltd., 2020)
Purpose Given the scarcity of Takaful products to provide financial preparation for flood victims, this study aims to propose an alternative Takaful model based on Waqf principle for the flood victims in Malaysia. This study serves as an initial stage to propose the above Takaful model and discusses the theoretical background of the model, which includes identifying the suitable Islamic principles and roles of parties involve in the model framework. Design/methodology/approach To achieve the said objectives, this paper reviews previous studies, opinions of scholars and existing Takaful models that are currently offered in the market. Findings In an effort to alleviate the financial burden of businesses and individuals affected by flood, Takaful industry needs to offer a special Takaful scheme to the flood victims and achieve its main objective to prepare a financial protection for social well-being. There is no harm for the various institutions (Takaful operators and State Islamic Religious Council) to do collaboration in realizing the Waqf-based Takaful model to ensure it is done in its original form to achieve the maqasid Shariah. Practical implications As an Islamic entity, the objective of Takaful business should focus on assisting the society in reducing their financial burden rather than just concentrating on achieving business profit. Thus, Waqf-based Takaful model would give platform to the operators to play their role in the society. Originality/value The views discussed in this paper originally from the researchers which is done by integrating the Islamic principles and roles of all stakeholders that may involve to implement Waqf-based Takaful model mainly for risk and financial protection for the future flood victims. The proposed framework discussed in this paper is in original form as a result of literatures and market practice in Malaysia.